Evaluation of Acetylcholine Esterase and Protease Inhibitory Potential of Sonchus oleraceus, Melia azedarach and Citrus sinensis - Rehman, Shafiq-ur-; Shahwar, Durre; Asam Raza, Muhammad; Saeed, Afifa; Ilyas, Faiza; Qaiser, Saba (Asian Journal of Chemistry, 2013)
Sonchus oleraceus (Family: Asteraceae), Melia azedarach (Family: Meleaceae) and Citrus sinensis (Family: Rutaceae) were extracted in methanol and partitioned with hexane, ethyl acetate and n-butanol successively. Acetylcholine esterase (AChE) and protease activities were carried out by reported methods. Ethyl acetate and methanol extract of the selected plants were active in the enzyme assays. The extracts of S. oleraceus exhibited significant results in proteases assay with % inhibition 90.2 ± 1.4, IC50 = 23 ± 1 μg (methanol extract) and 71.1 ± 1.6, IC50 = 45 ± 2 μg (ethyl acetate extract). The solvent extracts of M. azedarach and C. sinensis showed moderate results in the enzyme inhibition assays. Among all the solvent extracts of the selected plants, hexane and n-butanol extracts showed very low response.